Proceedings of the 14th International Conference on Human-Computer Interaction With Mobile Devices and Services 2012
DOI: 10.1145/2371574.2371624
|View full text |Cite
|
Sign up to set email alerts
|

PocketMenu

Abstract: We present PocketMenu, a menu optimized for non-visual, in-pocket interaction with menus on handheld devices with touch screens. By laying out menu items along the border of the touch screen its tactile features guide the interaction. Additional vibro-tactile feedback and speech allows identifying the individual menu items non-visually. In an experiment, we compared PocketMenu with iPhone's VoiceOver. Participants had to control an MP3 player while walking down a road with the device in the pocket. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Embedding haptic or tactile feedback in objects has been widely used to increase the user experience and interaction ca pabilities of mobile and physical computing devices [27]. For example, haptic feedback is utilized to offer physical feedback for visual controls [12,30,38,58,59,61] and icons [2,26], for rendering virtual textures and geometric features [1,24,40] and to implement shape-changing displays [7,57].…”
Section: Dynamic Tactile Feedback On Interactive Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedding haptic or tactile feedback in objects has been widely used to increase the user experience and interaction ca pabilities of mobile and physical computing devices [27]. For example, haptic feedback is utilized to offer physical feedback for visual controls [12,30,38,58,59,61] and icons [2,26], for rendering virtual textures and geometric features [1,24,40] and to implement shape-changing displays [7,57].…”
Section: Dynamic Tactile Feedback On Interactive Objectsmentioning
confidence: 99%
“…For instance, shape-changing displays make use of embedded mechanical [7,15], pneumatic [51] or mag netic [28] actuators, or the object itself is built from shapechanging materials [57]. Similarly, tactile interfaces have been realized by embedding actuators in the device [12,30,38,59,61]. This approach often suffers from low-resolution output.…”
Section: Dynamic Tactile Feedback On Interactive Objectsmentioning
confidence: 99%
“…We conduct an experiment to evaluate the effect of physical challenging activities on user perception of tactile textures. We consider five challenging activities that represent common situations where users often use their smartphones: (1) seated in an office [4], (2) standing in an office [11], (3) seated in the tramway [5], (4) standing in the tramway [10] and (5) walking in the street [24,27].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, they found that tactile feedback based technique has a key role in improving the touch interaction experience. Pielot et al [27] used vibrotactile feedback on a touchscreen device for an optimized eyes-free menu, and showed that, while walking, the improved menu with tactile feedback surpassed a replica of the iPhone's VoiceOver. Pohl et al [28] investigated the effect of compression feedback through pneumatic actuation on user attention when walking and taking a public transport.…”
Section: Haptic Feedback During Physical Challenging Activitymentioning
confidence: 99%
See 1 more Smart Citation